2018
DOI: 10.1021/acsami.8b03529
|View full text |Cite
|
Sign up to set email alerts
|

Tricolor White-Light-Emitting Carbon Dots with Multiple-Cores@Shell Structure for WLED Application

Abstract: The past few years have witnessed the rapid development of carbon dots (CDs) due to their outstanding optical properties and a wide range of applications. However, the design and control of CDs with long-wavelength multicolor emission are still huge challenges to be addressed for their practical use in different fields. Here, novel nitrogen-doped multiple-core@shell-structured AC-CDs with tricolor emissions of red, green, and blue were constructed via one-pot hydrothermal method from 5-amino-1,10-phenanthrolin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
63
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(64 citation statements)
references
References 60 publications
1
63
0
Order By: Relevance
“…The structure of LBE was analyzed by FT-IR spectroscopy, XPS, UV spectroscopy and mass spectrometry. The FT-IR spectrum ( Figure 1A) illustrated that LBE contained hydroxyl groups (3,285 cm −1 ), -CH 3 /-CH 2 groups (2,934 and 2,880 cm −1 ), benzene rings (1,608, 1,510 and 1,446 cm −1 ), -CH 3 groups (1362 cm −1 ), carbonyl groups (1,784 and 1,710 cm −1 ), C-O-C bonds (1,246 cm −1 ) and aromatic hydroxyl groups (1,064 cm −1 ; Bao et al, 2015;Zhang et al, 2018). XPS analysis showed that LBE contained C (46%) and O (54%) elements ( Figure 1B).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The structure of LBE was analyzed by FT-IR spectroscopy, XPS, UV spectroscopy and mass spectrometry. The FT-IR spectrum ( Figure 1A) illustrated that LBE contained hydroxyl groups (3,285 cm −1 ), -CH 3 /-CH 2 groups (2,934 and 2,880 cm −1 ), benzene rings (1,608, 1,510 and 1,446 cm −1 ), -CH 3 groups (1362 cm −1 ), carbonyl groups (1,784 and 1,710 cm −1 ), C-O-C bonds (1,246 cm −1 ) and aromatic hydroxyl groups (1,064 cm −1 ; Bao et al, 2015;Zhang et al, 2018). XPS analysis showed that LBE contained C (46%) and O (54%) elements ( Figure 1B).…”
Section: Resultsmentioning
confidence: 99%
“…XPS analysis showed that LBE contained C (46%) and O (54%) elements ( Figure 1B ). Following analysis of the high resolution XPS spectra of elemental C ( Figure 1C ) and O ( Figure 1D ), the binding energies of 532.28, 286, and 284.5 eV were attributed to O-C, C-O, and C-C/C=C bonds, respectively (Sheng et al, 2011 ; He et al, 2018 ; Miao et al, 2018 ; Zhang et al, 2018 ). The UV absorption spectrum of LBE ( Figure 1E ) contained n-π * and π-π * transitions between 190 and 400 nm (Bi et al, 2018 ; Miao et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…The comparison of our results with those of other studies is presented in Table S2. † [52][53][54][55][56][57][58] To explore the characteristics of GQD-based white LED in depth, the device spectrum of colour conversion layer is measured under different working currents. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…[ 2 ] Some wide band‐gap semiconductors, such as gallium nitride and indium gallium nitride, are used for violet LEDs, which are irreversible harm to people and quite expensive. [ 8,9 ] Recently, Cd 2+ or Pb 2+ based colloidal semiconductor quantum dots (QDs) have emerged as candidates for efficient violet LEDs. [ 10–12 ] Table S1 (Supporting Information) summarizes the key optical parameters of these QD based violet emitters and the corresponding external quantum efficiency (EQE) of solution‐processing LEDs.…”
Section: Introductionmentioning
confidence: 99%